Refleksi Filosofis tentang "Pandangan Dunia" Di Balik Pergelaran Tayub - Pitoyo, Djoko (Jurnal Filsafat "WISDOM", 2003)
Tayub is one of the Javanese performing arts and it is widely known among people in rural areas. Despite the fact that today it is commonly perceived as a form of popular entertaintment, it has initially served as a sacred dance, intended to encourage such a magical attraction as fertility either agricultural plant fertility or marital fertility as well for general safety.A world view underlying this performing art is a mythical one, in which it assumes that the world as a whole is being dominated by supernatural power. As this power can be either friendly or hostile, a ritual performance like Tayub is perceived to be necessary as a way ti create a good relationship or to resolve a tension between human being and the world dominated by supernatural power.